2014
DOI: 10.1002/cbin.10326
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hippocampal astrocytes mediation of spatial memory and theta rhythm by gliotransmitters and growth factors

Abstract: Our knowledge about encoding and maintenance of spatial memory emphasizes the integrated functional role of the grid cells and the place cells of the hippocampus in the generation of theta rhythm in spatial memory formation. However, the role of astrocytes in these processes is often underestimated in their contribution to the required structural and functional characteristics of hippocampal neural network operative in spatial memory. We show that hippocampal astrocytes, by the secretion of gliotransmitters, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 96 publications
(169 reference statements)
0
11
0
Order By: Relevance
“…To date, several groups have confirmed that SRR is expressed by inhibitory and excitatory neurons throughout the mammalian brain (12, 19, 33), where neuronal d-serine is mainly released in response to depolarization (20). with an increase in hippocampal θ power at rest as opposed to a decrease in θ power after severe TBI (44,45). In this regard, our mild-to-moderate CCI model involving synaptic damage without neuronal losses is more akin to models of progressive synaptic dysfunction, such as AD models, where injury results in a marked increase in θ power associated with increased astrocytic d-serine levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To date, several groups have confirmed that SRR is expressed by inhibitory and excitatory neurons throughout the mammalian brain (12, 19, 33), where neuronal d-serine is mainly released in response to depolarization (20). with an increase in hippocampal θ power at rest as opposed to a decrease in θ power after severe TBI (44,45). In this regard, our mild-to-moderate CCI model involving synaptic damage without neuronal losses is more akin to models of progressive synaptic dysfunction, such as AD models, where injury results in a marked increase in θ power associated with increased astrocytic d-serine levels.…”
Section: Discussionmentioning
confidence: 93%
“…In this regard, our mild-to-moderate CCI model involving synaptic damage without neuronal losses is more akin to models of progressive synaptic dysfunction, such as AD models, where injury results in a marked increase in θ power associated with increased astrocytic d-serine levels. Alternatively, impaired NMDAR activation on parvalbumin-positive interneurons can result in the changes observed (44). Interestingly, whereas NMDAR hypofunction impairs hippocampal θ oscillations, increased activation of neuronal NMDARs due to increased availability of d-serine after injury can potentially enhance θ oscillations (46).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated the particularity and interconnected functionality of hippocampal neurons and astrocytes, suggesting the possibility of region-specific alterations involving the two cell types. Both neurons and astrocytes, as well as their interactions, were implicated in learning and memory processes localized in the hippocampus (Henneberger et al 2010;Suzuki et al 2011;Ota et al 2013;Hassanpoor et al 2014;Tadi et al 2015;Gao et al 2016;Pabst et al 2016). Astrocytes were further shown to contribute to the integration of adult-born neurons in the hippocampus, although adult hippocampal neurogenesis in humans remains controversial (Krzisch et al 2015;Sultan et al 2015;Sorrells et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As it is known that the dorsal hippocampus (e.g., CA3) is essential once the critical time window requires spatial memory for a longer time period (i.e., 5 min; Lee and Kesner, 2003; Yoon et al, 2008; Shipton et al, 2014), it is not surprising that TAT-Gap19 impairs spatial short-term memory. Indeed, as discussed further, hippocampal astrocytes mediate spatial memory through the release of gliotransmitters (Hassanpoor et al, 2014). TAT-Gap19 presumably does not affect spatial working memory since the hippocampus and medial prefrontal cortex jointly contribute to working memory/cognition (Moser et al, 2015) and other associational sensory cortices than the dorsal hippocampus could still provide information on sensory cues to the medial prefrontal cortex (Lee and Kesner, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…TAT-Gap19 presumably does not affect spatial working memory since the hippocampus and medial prefrontal cortex jointly contribute to working memory/cognition (Moser et al, 2015) and other associational sensory cortices than the dorsal hippocampus could still provide information on sensory cues to the medial prefrontal cortex (Lee and Kesner, 2003). Furthermore, in the hippocampus, the structured network of place cells and grid cells (Moser et al, 2015), which is crucial for spatial memory formation, might be more vulnerable for gliotransmitter modulation (Hassanpoor et al, 2014). …”
Section: Discussionmentioning
confidence: 99%